The relationship between vocational college students’ liking of teachers and learning engagement: A moderated mediation model - Lu, Lei; Zhang, Luyao; Wang, Longmei (Frontiers in Psychology, 2022)
To clarify the relationship between higher vocational students’ liking of teachers and their learning engagement, based on the theory of social exchange, 1279 vocational students in the Yangtze River Delta and the Pearl River Delta in China are used as the research objects. From the perspective of students and teachers, SPSS and AMOS are used to conduct a two-stage linear regression analysis. The results show that (1) students’ liking of their teachers has a positive effect on learning engagement; (2) liking positively affects students' psychological empowerment; (3) liking of teachers indirectly influences learning engagement through psychological empowerment; (4) teacher support positively moderate the indirect relationship between liking of teachers and learning engagement through psychological empowerment. This study attempts to provide practical guidance for college students to provide learning engagement.